Motivation among Muslim in paying Zakat on income at Kota Kinabalu, Sabah / Natasha Noorain binti Kosno - Kosno, Natasha Noorain (Faculty of Business Management, Universiti Teknologi MARA, 2011)
Different with alms (sedeqah), zakat is one of the pillars which every Muslim obligatory to pay it according to person's eligibility whereby alms, matter which been encourage to perform by religious. Parallel with nowadays development, transaction of paying zakat much easier compare to the period of Nabi Muhammad SAW. However, lack of motivation among Muslim in paying zakat shows from the number of people paying zakat. For this research, it focus more on zakat on income which the common transaction among working people. Aim for this study to determine and find out what possibly can makes a person to pay zakat on income. The researcher used survey questionnaire to colle,ct data from potential respondents and from the results, there are four reasons that influence a person to perform zakat on income which are job sector, obligation, reward, and zakat institution. The first reason, obligation with the highest score of mean, 4.83, shows Muslim agreed they responsibility towards religious matter makes them pay their zakat in income. Followed by reward, with 4.68 mean, next 4.53 mean, belongs to zakat institution and last but not least, 4.26 mean by job sector. In other words, to practice zakat on income not only due obligation towards religious alone but job sector that person gets involved with together with zakat institution play important role to enhance the number payer of zakat. Allah says in surah al Baqarah (2:110), "And be steadfast in prayer and regular in charity: And whatever good ye send forth for your souls before you (ye shall find it with God: for God sees Well all that ye do ... "